Planning for Islamic Education Supervision Joyful Learning Digital Media Based on Love in Elementary Madrasahs - Tiara Listari; Ahmad Zainuri (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The development of digital technology has encouraged Islamic elementary schools (Madrasah Ibtidaiyah) to develop innovative and humanistic Islamic education learning. A joyful learning approach based on digital media and the value of love is used as an alternative way to create a pleasant and meaningful learning atmosphere. This article aims to examine the planning of Islamic education supervision in supporting the implementation of joyful learning using digital media based on love in Islamic elementary schools. This research also uses a qualitative approach with a literature study method through analysis of various relevant literature. The results of the study indicate that structured, collaborative supervision planning based on the value of compassion (rahmah) can improve the quality of learning and strengthen the Islamic character of students.